Childhood-onset borderline tuberculoid leprosy with reversal reaction - Lubis, Ramona D; Darmi, Mila; Chandra, Rudi (Journal of General - Procedural Dermatology and Venereology Indonesia, 2021)
Background: Leprosy is a chronic granulomatous infection caused by Mycobacterium lepraethat predominantly affects the skin and peripheral nerves. Leprosy among children is still common in endemic countries. Case Illustration: A 12-year-old girl complained about a hypopigmented anesthetic patch on her face for 11 years, which became larger and spread slowly to her arms and legs. She had a history of close contact with her aunt, who was diagnosed with multibacillary leprosy. On slit-skin-smear test, acid-fast-bacilli (bacteriologic index +1) were found. She was diagnosed with multibacillary leprosy and treated with children’s multidrug therapy-multibacillary (MDT-MB) regimen. After 2 months of MDT-MB treatment, she complained that the hypopigmented patches became reddish and swollen with enlarged peripheral nerves. She underwent a reversal reaction (RR) and was treated with 40 mg prednisone daily and continued the MDT regimen. Discussion: RR is found less frequently in children than the adult.Accurate diagnosis is vital because of its psychosocial impact on the family. One of the most prominent features of borderline tuberculoid leprosy is its susceptibility to RR. It is characterized by rapid changes from existing plaques to edematous lesions with or without abrupt neuritis. Conclusion: We reported a girl with borderline tuberculoid leprosy with developed RR after taking MDT-MB for 2 months. The risk factors for developing RR were being diagnosed with borderline tuberculoid leprosy, female, multiple and disseminated patches involving larger body areas and multiple nerve involvement, large facial patches, and starting treatment. These risk factors were found in our patient.